The interleukin-1 axis and the tumor immune microenvironment in pancreatic ductal adenocarcinoma - Kelly M. Herremans (Neoplasia: An International Journal for Oncology Research, 2022)
Interleukin-1 (IL-1) plays a key role in carcinogenesis and several IL-1-targeted therapeutics are under investigation for the treatment of pancreatic ductal adenocarcinoma (PDAC). We sought to broaden our understanding of how the family of IL-1 ligands and receptors impact the tumor immune landscape and patient survival in PDAC. Gene expression data and DNA methylation data for IL1A, IL1B, IL1RN, IL1R1, IL1R2, and IL1RAP was attained from The Cancer Genome Atlas (TCGA) database and cross validated using the National Center for Biotechnology Information (NCBI) Gene Expression Omnibus (GEO) database. Immune cell-type abundance was estimated using CIBERSORTx. Further confirmatory soluble protein analysis and peripheral blood immunophenotyping were performed on available tissue samples from our institution. 169 PDAC patients and 50 benign pancreatic TCGA-based samples were analyzed. IL1A (p < 0.001), IL1RN (p < 0.001), IL1R2 (p < 0.001), and IL1RAP (p = 0.006) were markedly increased in PDAC tumor tissue compared to benign pancreatic tissue. Furthermore, expression of IL1A, IL1B and IL1R1 were positively correlated with gene expression of immune checkpoints PVR, CD274, CD47, CD80, and HLA-A/B/C (p < 0.001). IL1B and IL1R1 were correlated to expression of PDCD1, CD86, CTLA4 and IDO1 (<0.001). Low expression of IL1RN (p = 0.020), IL1R2 (p = 0.015), and IL1RAP (p = 0.003) and high expression of IL1B (p = 0.031) were correlated with increased patient survival. At the protein level, IL-1β was correlated with increased peripheral central memory CD4+ and CD8+ T-cells as well as decreased Th2 cells. These findings suggest that the IL-1 axis plays a complex and pivotal role in the host immune response to PDAC.